Impact of RAAS Inhibitors on Clinical Outcome and Mortality in Patients With STEMI During the COVID-19 Era: A Multicenter Observational Study - Barbieri, Lucia; Trabattoni, Daniela; Stefanini, Giulio G.; Vizzardi, Enrico; Tumminello, Gabriele; Assanelli, Emilio; Adamo, Marianna; Pivato, Carlo A.; Provenzale, Giovanni; Gentile, Domitilla; Metra, Marco; Carugo, Stefano (Frontiers in Cardiovascular Medicine, 2021)
Conflicting results are available regarding the influence of ACEi/ARBs on the risk of COVID-19 infection, while less is known about their impact on clinical outcome of STEMI patients with confirmed diagnosis of COVID-19. Our aim was to evaluate the impact of ACEi/ARBs therapy on in-hospital mortality and clinical outcomes of STEMI patients during COVID-19 pandemic. We retrospectively analysed consecutive STEMI patients hospitalised from February 20, to May 10, 2020 at four Hospitals in Lombardy. SARS-COV-2 diagnosis was performed by nasopharingeal swab test. Procedural outcome, respiratory complications and in-hospital mortality were reported. Univariate and multivariate analysis were performed by logistic regressions. Our population was represented by 182 STEMI patients, 76.9% male, mean age 67+/-12.5. Hypertension was reported in 53.3%, treated with ACEi/ARBs in 29.1%. COVID-19 diagnosis was confirmed in 17.1%. In-hospital mortality (13.2%) was significantly higher in COVID-19 patients (31% vs 10%, p=0.003), even if ejection fraction (OR 0.93[95%CI]0.87–0.99;p=0.03) and respiratory complications (OR 9.39[95%CI]1.91–45.9; p=0.006) result the only two independent predictors. The incidence of COVID-19 infection was not influenced by ACEi/ARBs (16.5% in naïve vs 18.8%) whose presence at admission did not correlate with respiratory complications or mortality both in case of discontinuation or manteinance. In conclusion, in a high-risk population, such as that of STEMIs, the potential benefit of ACEi/ARBs discontinuation in COVID-19 patients is overcome by its detrimental effect. Intensive care, additional preventive respiratory investigations, regardless from swab test result, should be suggested among all patients admitted for STEMI during pandemic.